IMPLEMENTASI NILAI-NILAI KEADILAN DALAM MASYARAKAT: Suatu Kajian Filsafat Hukum - -, Kiljamilawati (Jurnal Ilmiah Ecosystem, 2016)
The nature of the law is based on the idea of Justice and moral force. The idea ofJustice is never separated from the relation of the law, because the law clearly discuss orvague is always talk about justice. Power is also the moral elements of the nature of thelaw, because in the absence of morality so will lose its independent and supremacy.Justice and injustice according to law will be measured and assessed by referring to thedignity of morality and human dignity.